Fifteen years of IOL exchange: indications, outcomes, and complications. Issue 12 (December 2020) - Goemaere, Jordy; Trigaux, Céline; Denissen, Laurens; Dragnea, Diana; Hua, Minh-Tri; Tassignon, Marie-José; Dhubhghaill, Sorcha Ní
Abstract : This article reports the indications, frequency, and outcomes regarding IOL exchange in 2 university hospital settings over a period of 15 years. Abstract : Purpose: To report the indications, frequency, and outcomes regarding intraocular lens (IOL) exchange in 2 university hospital tertiary referral settings over a period of 15 years. Setting: Ophthalmology departments of the University Hospital Antwerp and the University Hospital Leuven, Belgium. Design: Retrospective cross-sectional study. Methods: In this retrospective study, included were patients who underwent an IOL exchange between 2002 and 2017. Patient demographics, surgical indication, comorbidities, visual outcomes, and complications were reported. Patients who underwent IOL repositioning or add-on IOL implantation or extraction, and patients who were left aphakic, were excluded. Results: Included in the study were 492 eyes. The mean age was 66.0 ± 13.3 years (range 19–91 years). The mean time between primary surgery and IOL exchange was 54.61 ± 67.07 months (range 0–343 months). Primary indication for explantation was IOL opacification, and the most common ophthalmic comorbidity was a previous history of vitreoretinal surgery. Preoperatively, the mean uncorrected visual acuity (UCVA) and corrected distance visual acuity (CDVA) were 0.47 ± 0.27 (range 0–1) and 0.61 ± 0.32 (range 0–1.2), respectively. Postoperative UCVA and CDVA was 0.7 ± 0.3 (range 0–1.2) and 0.8 ± 0.28 (range 0.05–1.6), respectively. The increase in both CDVA and UCVA was statistically significant ( P < .001, paired t test). The most common complication perioperatively was vitreous prolapse, which occurred in 61 eyes (16%). Conclusions: IOL exchange is a challenging yet valuable treatment option for a wide spectrum of problematic IOL outcomes. The most common indication remains IOL opacification, although IOL dislocation and patient dissatisfaction are increasing as indications.